Weed’s Vegetation Analysis of Centella (Centella asiatica L. Urban) Plantations - Dian Susanti; Devi Safrina; Nur Rahmawati Wijaya (Caraka Tani: Journal of Sustainable Agriculture, 2021)
Centella (Centella asiatica L. Urban) originally is a wild plant that is being cultivated to be medicinal and cosmetics raw material. The process of centella cultivation is relatively easy and can be grown in a variety of altitudes. One obstacle in centella cultivation is weed growth. The proper handling of weeds in centella plantation requires data on the weed types and characteristics. This research aimed to determine the weed types and the amount of weed found in centella cultivation. Sampling was carried out purposively based on the presence of weeds in the cultivation area. Weed inventory was carried out using linear vegetation methods in 12 plantation beds of centella, with a size of 6 x 2 m2 each. Observations were made during weeding on one cropping season. Weed inventory was carried out by recording the number of species and number of individual weed and taking documentation of weeds that were recorded for identification purposes. Research data were analyzed by using vegetation analysis. The weed vegetation analysis on centella plantations showed that there were 35 species of weeds identified from 20 plant families. Cyperus rotundus L. dominates the weed vegetation in centella plantations because of its high adaptability and its allelochemical exudates. To sustainably cultivate the centella, proper techniques of weed controls need to be applied by considering the nature of Cyperus rotundus L.